Pengaruh Retardan Paklobutrazol terhadap Pertumbuhan dan Pemulihan Dua Aksesi Ubi Kayu - Surya Diantina; Darda Efendi; Ika Mariska (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2015)
Normal growth medium is not effective for in vitro conservation due to the risk of somaclonal variation that may increase dueto short interval between subculture. Two experiments involving growth retardant paclobutrazol (PBZ) were conducted toreduce explants growth and extend subculture interval. In order to develop medium-term conservation of cassava, therecovery of plantlets after in vitro storage was also observed. Accession 433 and 450 were used in two independentexperiments. Completely Randomized Design was used with three replications. PBZ at 0, 3.4, 6.8, and 10.2 μM weresupplemented onto MS medium + arginin 100 ppm. Observation was done on shoot length, number of nodes and leaves, andnumber of white and senescence leaves. The results showed that after nine months without subculture, both cassavaaccessions showed different results in in vitro growth and their recovery. PBZ 3.4 μM performed as the best treatment inaccession 433 and 450 to reduce in vitro growth and their recovery after storage.